2020
DOI: 10.1155/2020/7864721
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc-α2-Glycoprotein Levels in Patients with or without Coronary Artery Disease in Chinese North Population

Abstract: Coronary artery disease (CAD), the leading cause of morbidity and mortality, has imposed huge health and economic burdens globally. Zinc-α2-glycoprotein (ZAG) is a novel adipokine. Increasing evidence suggests the close relationship between serum ZAG levels and various cardiometabolic risk factors. However, the relationship between serum ZAG levels and CAD is still not fully clarified. We conducted this study to evaluate serum ZAG levels and its association with cardiovascular risk factors. A total of 129 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Despite numerous studies on FNDC5 variants ( 21 , 45 ), the biological function of these forms is still poorly understood. Studies have confirmed that irisin can promote white adipose tissue browning ( 13 , 46 ), stimulate lipolysis ( 47 49 ), and thus play a critical role in regulating energy homeostasis ( 50 ). Therefore, we examined the biological activity of r-sFNDC5 on browning and lipid metabolism in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies on FNDC5 variants ( 21 , 45 ), the biological function of these forms is still poorly understood. Studies have confirmed that irisin can promote white adipose tissue browning ( 13 , 46 ), stimulate lipolysis ( 47 49 ), and thus play a critical role in regulating energy homeostasis ( 50 ). Therefore, we examined the biological activity of r-sFNDC5 on browning and lipid metabolism in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%